Evaluasi Permasalahan Kekuatan Splicing Benang pada Mesin Winding PT INS dengan Metode Seven Tools - Khairunnisa, Hasna; Triwidiyanto, Fahri; Aribowo, Irham (Teknik Industri Universitas Ma Chung, 2023)
Yarn manufacturing engineering stands as one of the initial phases in the textile industry and holds considerable significance in determining subsequent process qualities. PT INS specializes in producing ring spun yarn, wherein the final stage integrates an automatic yarn quality control mechanism within the winding machine. When the sensor identifies any yarn irregularity, an automatic cutting process initiates. Additionally, the winding machine incorporates a yarn splicing procedure to reconnect separated yarn ends or join yarn during cop changes. Any flaw in this splicing process can lead to a weak yarn splice, evident in the diminished Retained Spliced Strength (RSS), which in turn impacts subsequent weaving and knitting processes. PT INS encountered a yarn splicing issue, evidenced by consistently low RSS values from each spindle on its winding machines. An analysis was conducted employing various tools, including Control Charts, Fishbone Diagrams, Check Sheets, and Pareto Diagrams, to pinpoint the problematic spindle and identify the root cause of the splicing problem. Subsequently, improvement measures were proposed based on the analysis of each contributing factor. These steps aim not only to enhance the splicing process within the winding machine but also to elevate overall yarn quality. Through this approach, PT INS aims to rectify the splicing discrepancies, ultimately ensuring a more robust splicing process within the winding machine and elevating the overall yarn quality.